Incidence and Mortality Following Hip Fracture in Korea - Yoon, Hyun-Koo; Park, Chanmi; Jang, Sunmee; Jang, Suhyun; Lee, Young-Kyun; Ha, Yong-Chan (Journal of Korean medical science, 2011)
The authors evaluated the incidence of hip fracture and subsequent mortality in Korea using nationwide data obtained from the Health Insurance Review and Assessment Service. This study was performed on patient population, aged 50-yr or older who underwent surgical procedures because of hip fracture (ICD10; S720, S721). All patients were followed using patient identification code to identify deaths. Crude hip fracture rates increased from 191.9/100,000 in 2005 to 207.0/100,000 in 2008 in women and from 94.8/100,000 in 2005 to 97.8/100,000 in 2008, in men respectively. Crude mortality within 12 months after hip fracture showed a similar trend (18.8% in 2005 and 17.8% in 2007). The mean of standardized mortality ratio of hip fracture was 6.1 at 3 months, 3.5 at 1 yr, and 2.3 at 2 yr post-fracture. The increasing incidence and the high mortality after hip fracture are likely to become serious public health problems and a public health program should begin to prevent hip fractures in Korea.